Graphene/Polyurethane Nanocomposites for Improved Gas Barrier and Electrical Conductivity - Kim, Hyunwoo; Miura, Yutaka; Macosko, Christopher W (Chemistry of materials, 2010)
Recently developed strategies for isolating single-layer carbon sheets from graphite have enabled production of electrically conductive, mechanically robust polymer nanocomposites with enhanced gas barrier performance at extremely low loading. In this article, we present processing, morphology, and properties of thermoplastic polyurethane (TPU) reinforced with exfoliated graphite. For the first time, we compare carbon sheets exfoliated from graphite oxide (GO) via two different processes: chemical modification (isocyanate treated GO, iGO) and thermal exfoliation (thermally reduced GO, TRG), and three different methods of dispersion: solvent blending, in situ polymerization, and melt compounding. Incorporation of as low as 0.5 wt % of TRG produced electrically conductive TPU. Up to a 10-fold increase in tensile stiffness and 90% decrease in nitrogen permeation of TPU were observed with only 3 wt % iGO, implying a high aspect ratio of exfoliated platelets. Real- and reciprocal-space morphological characterization indicated that solvent-based blending techniques more effectively distribute thin exfoliated sheets in the polymer matrix than melt processing. This observation is in good qualitative agreement with the dispersion level inferred from solid property enhancements. Although also processed in solvents, property increase via in situ polymerization was not as pronounced because of reduced hydrogen bonding in the TPU produced.